ANALYSIS OF THE MODERN RUSSIAN MARKET OF EDUCATIONAL SERVICES: CHALLENGES AND DEVELOPMENT TRENDS - Avtsinova, Galina; Nikiporets-Takigawa, Galina; Zhaleiko, Kristina (Revista Inclusiones, 2020)
The article has been devoted to analyzing some problems related to the Russian market of educational services functioning in the context of the rapid development of digital technologies, digitalization of the economy, education and society. This actualizes the issue of training highly qualified personnel, whose activities should comply with new requirements of the digital civilization, as well as new challenges and risks. The aim of the article has been to study the transformation of areas, peculiarities of providing educational services, educational technologies, and competencies in the main educational programs of higher education in the modern Russia in the context of digital realities, as well as to develop some solutions for updating the educational services market, improving the quality of education, and erudition of the society. Websites of the largest higher educational establishments of the country, including those located in the Orenburg region, have been analytically monitored for identifying the focus of educational programs and services on the consumer needs and preferences. The authors have come to the conclusion that it is necessary for all specialists, including humanitarians, to acquire digital competence.